Sustainability of an in situ aided phytostabilisation on highly contaminated soils using fly ashes: Effects on the vertical distribution of physicochemical parameters and trace elements. (15th April 2016) - Bidar, Géraldine; Waterlot, Christophe; Verdin, Anthony; Proix, Nicolas; Courcot, Dominique; Détriché, Sébastien; Fourrier, Hervé; Richard, Antoine; Douay, Francis
Abstract: Aided phytostabilisation using trees and fly ashes is a promising technique which has shown its effectiveness in the management of highly metal-contaminated soils. However, this success is generally established based on topsoil physicochemical analysis and short-term experiments. This paper focuses on the long-term effects of the afforestation and two fly ashes (silico-aluminous and sulfo-calcic called FA1 and FA2, respectively) by assessing the integrity of fly ashes 10 years after their incorporation into the soil as well as the vertical distribution of the physicochemical parameters and trace elements (TEs) in the amended soils (F1 and F2) in comparison with a non-amended soil (R). Ten years after the soil treatment, the particle size distribution analysis between fly ashes and their corresponding masses (fly ash + soil particles) showed a loss or an agglomeration of finer particles. This evolution matches with the appearance of gypsum (CaSO4 2H2 O) in FA2m instead of anhydrite (CaSO4 ), which is the major compound of FA2. This finding corresponds well with the dissolution and the lixiviation of Ca, S and P included in FA2 along the F2 soil profile, generating an accumulation of these elements at 30 cm depth. However, no variation of TE contamination was found between 0 and 25 cm depth in F2 soil except for Cd. Conversely, Cd, Pb, Zn and Hg enrichment was observed at 25 cm depth in the F1 soil, whereas no enrichment was observed for As. The fly ashes studied, and notably FA2, were able to reduce Cd, Pb and Zn availability in soil and this capacity persists over the time despite their structural and chemical changes. Highlights: Anhydrite in ashes disappeared instead of gypsum in ash masses after a decade. Ca, S and P in sulfo-calcic ash were dissolved and their leaching in soil occurred. Enrichment in metals and metalloid was noted in the first 25 cm of soil. Metal availability decreased with the depth in sulfo-calcic ash amended soil.